Case report: Balloon compression for cervical chyle leakage post neck dissection - Ding, Zhaoming; Chen, Mengshi; Pang, Rui; Sheng, Ruinan; Zhao, Xuesong; Nie, Chunlei (Frontiers in Surgery, 2022)
Postoperative chyle leakage (CL) is a rare but severe complication after neck dissection, and most patients with this complication can be treated conservatively. However, in patients with high-flow leakage, efficient and well-tolerated conservative treatment options are still lacking, and the treatments can be complicated. In this study, we report a case with CL of 1100 ml/day after neck dissection that was successfully treated by balloon compression.